2021
DOI: 10.3390/jcm10010152
|View full text |Cite
|
Sign up to set email alerts
|

Denosumab Discontinuation and the Rebound Phenomenon: A Narrative Review

Abstract: Denosumab is a potent antiresorptive agent that substantially increases bone mineral density and reduces fracture rates at all skeletal sites for as long as it is administered. However, its favorable skeletal effects reverse quickly upon its discontinuation, because of a vast increase of osteoclast number and activity, which leads to a subsequent profound increase of bone turnover above pre-treatment values, a phenomenon commonly described as “rebound phenomenon”. More importantly, most patients experience rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
15

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 83 publications
2
69
0
15
Order By: Relevance
“…We also acknowledge that the use of teriparatide may be limited by cost, its required daily injections and its contraindications such as a prior history of skeletal malignancy or radiotherapy (79). Denosumab may not be a preferred first-line option for GIOP, as discontinuation is associated with a rapid loss of effectiveness and there is some limited data to suggest that fracture risk might be transiently increased (80)(81)(82). Anti-osteoporosis therapy is often stopped after GCs are discontinued, as discussed in the following section.…”
Section: Clinical Guideline Recommendations For Starting Treatment To Prevent Giop: Who To Treat and Which Therapymentioning
confidence: 99%
“…We also acknowledge that the use of teriparatide may be limited by cost, its required daily injections and its contraindications such as a prior history of skeletal malignancy or radiotherapy (79). Denosumab may not be a preferred first-line option for GIOP, as discontinuation is associated with a rapid loss of effectiveness and there is some limited data to suggest that fracture risk might be transiently increased (80)(81)(82). Anti-osteoporosis therapy is often stopped after GCs are discontinued, as discussed in the following section.…”
Section: Clinical Guideline Recommendations For Starting Treatment To Prevent Giop: Who To Treat and Which Therapymentioning
confidence: 99%
“…Another anti-resorptive agent, denosumab (RANKL inhibitor), can also result in bone necrosis [ 23 ]. One special concern for denosumab is that its discontinuation is associated with a subsequent profound increase of bone turnover above pre-treatment values due to a substantial increase in OC number and activity, resulting in a risk of multiple vertebral fractures [ 24 , 25 ]. In addition, both bisphosphonates and denosumab do not effectively prevent focal joint destruction in human RA [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike bisphosphonates, denosumab is not incorporated into the bone, so its effect on bone turnover markers, BMD, and This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as: Aras B, Kuzu Ö. histomorphometric measurements is reversible (9)(10)(11). In a previous study, it was shown that iliac bone biopsies performed in patients using denosumab had no adverse effects on bone mineralization, lamellar bone formation and bone microarchitecture (12).…”
Section: Discussionmentioning
confidence: 99%